Eksplorasi Strategi Pembelajaran Kontekstual Berbasis AI dalam Pendidikan Agama Islam: Desain dan Implementasi - Muhammad, Devy Habibi; Hardiansyah, Yayak; Gofar, Abd.; Ali, Mahfud (Journal of Education and Learning Innovation, 2025)
The rapid development of digital technology, particularly artificial intelligence (AI), has brought significant changes to the field of education, including Islamic Religious Education (IRE). One of the main challenges faced by IRE in the digital era is delivering learning that remains relevant to students’ real-life experiences while effectively internalizing Islamic values in a meaningful way. Contextual learning is considered a strategic approach because it connects instructional content with students’ lived realities, while the use of AI offers opportunities for personalization, interactivity, and adaptive assessment. This study aims to explore the design and implementation of AI-based contextual learning strategies in Islamic Religious Education within formal educational settings. The research employs a qualitative descriptive method, with data collected through classroom observations, in-depth interviews with educators, and a review of relevant literature. The findings indicate that the integration of AI into contextual IRE learning enhances students’ understanding of Islamic values through the use of interactive simulations, da‘wah chatbots, and adaptive learning platforms that adjust content according to students’ needs and characteristics. Moreover, this strategy contributes to increased student engagement and moral reflection. However, its implementation requires adequate digital infrastructure, continuous professional development for teachers in technological literacy, and a flexible curriculum that is responsive to technological advancements. The implications of this study suggest that AI-based contextual learning holds significant potential as both a pedagogical and spiritual innovation in Islamic Religious Education to address the challenges of education in the digital era.